Using Computer-Based Timeline Media to Teach English Tenses - Teopilus, Susana; Tedjasuksmana, Hendra; Lestariningsih, Diana (Beyond Words, 2019)
The difference between English and Indonesian in the aspect of verb forms poses a big problem to Indonesian learners in learning the English Tenses. Indonesian learners are often unaware of the English time concept which affects verb forms. To overcome the problem, in this three-year research, Teopilus et al. have developed computer-based timeline media to teach the English Tenses. To find out the effectiveness of the developed media, 251 students from 4 (four) different senior high schools were given the instructions of the English Tense(s) using the timeline media. These subjects were given a pretest prior to the instruction and a posttest after it. The pretest scores and the posttest scores were statistically compared using the t-test formula. To obtain the users’ opinions on the developed media, a questionnaire was distributed to 7 (seven) English teachers. The results of the data analysis yield the following findings: (1) There is a significant increase from the average of the subjects’ pre-test scores to their post-test scores, and (2) The results of the users’ questionnaires also give positive responses to the developed timeline media. This implies that the computer-based timeline media developed in this research helps Indonesian learners comprehend the English Tenses better